Mapping Perceptual Value Shifts in Timepieces through Lifestyle Associations - Sengupta, Debashish; Titus, Ray (Indian Journal of Marketing, 2013)
Due to an increase in the number of products in the market, as well as owing to the changes in living conditions and lifestyles, there's been an array of products symbolizing and catering to those keen on living and exhibiting certain lifestyles. Amongst others, the increase in spare time, growth in disposable incomes, changes to work structure and greater incidence of stress, and also due to the manipulative adverts of companies as part of an increasingly sophisticated marketing mix, marketing value proposition today induces lifestyle consumption. Marketers have begun to realize that merely catering to functional sensibilities of consumers via products and services is no guarantee to a sale. Aesthetics and sensual sensibilities have taken prime places in the creation of consumer solutions. This means that marketers have had to place greater emphasis on brand building and engaging at an emotional level with the consumers keen on exhibiting their lifestyles.